2016
DOI: 10.3109/09593985.2015.1138009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of virtual reality-based balance exercises and conventional exercises on balance and fall risk in older adults living in nursing homes in Turkey

Abstract: Similar improvements were found in balance and fall risk with VR-based balance training and conventional balance training in older adults living in the nursing home. Both exercise trainings can be preferable by health care professionals considering fall prevention. Appropriate patient selection is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
130
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(146 citation statements)
references
References 40 publications
1
130
0
4
Order By: Relevance
“…Because the incidence of falls in nursing homes is not a typical Dutch healthcare problem and the extra care activities reported (e.g., examination of the resident, inform the doctor and the residents' family, administration, extra help with activities of daily living and contact with other disciplines) have to be conducted everywhere. Worldwide, there is attention for falls prevention in long‐term care facilities (Heinrich, Rapp, Rissmann, Konig, & Becker, ; Heinrich, Rapp, Stuhldreher et al., ; Vandenberg, van Beijnum, Overdevest, Capezuti, & Johnson, ; Yesilyaprak, Yildirim, Tomruk, Ertekin, & Algun, ). Also, studies from other countries showed that falls in nursing homes increase healthcare costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the incidence of falls in nursing homes is not a typical Dutch healthcare problem and the extra care activities reported (e.g., examination of the resident, inform the doctor and the residents' family, administration, extra help with activities of daily living and contact with other disciplines) have to be conducted everywhere. Worldwide, there is attention for falls prevention in long‐term care facilities (Heinrich, Rapp, Rissmann, Konig, & Becker, ; Heinrich, Rapp, Stuhldreher et al., ; Vandenberg, van Beijnum, Overdevest, Capezuti, & Johnson, ; Yesilyaprak, Yildirim, Tomruk, Ertekin, & Algun, ). Also, studies from other countries showed that falls in nursing homes increase healthcare costs.…”
Section: Discussionmentioning
confidence: 99%
“…Because the incidence of falls in nursing homes is not a typical Dutch healthcare problem and the extra care activities reported (e.g., examination of the resident, inform the doctor and the residents' family, administration, extra help with activities of daily living and contact with other disciplines) have to be conducted everywhere. Worldwide, there is attention for falls prevention in long-term care facilities Heinrich, Rapp, Stuhldreher et al, 2013;Vandenberg, van Beijnum, Overdevest, Capezuti, & Johnson, 2016;Yesilyaprak, Yildirim, Tomruk, Ertekin, & Algun, 2016 Another limitation is that we only estimated the extra staff time and costs until 1 year after the fall. In the more severe categories of injury, these will add a substantial cost due to permanent loss of mobility and other reductions in activities of daily living (Muller et al, 2015).…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
“…However, a clear shift to making more safe decisions was observed for all participants. In general, due to the lower number of subjects in different studies, the generalization of the results are somewhat restricted (Yeşilyaprak et al, 2016). Mattan et al (2017) discussed that age is associated with reduced perspective-taking capacity.…”
Section: Strengthmentioning
confidence: 99%
“…As mentioned before, most of the studies lack an adequate number of participants which makes it hard to generalize the efficacy of results. Future studies should use a larger sample size and consider culture and gender-oriented tasks (Vallejo et al, 2017;Yeşilyaprak et al, 2016). Future studies should also have appropriate dosages of use to improve the validity of treatment prescription and safe functioning levels of the seniors (Cardinale, 2018).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…This genre of games is referred to as exercise games, or exergames as they need the player to use their body movements to play. In addition, in compare to conventional balance exercise exegame is more effective [17]. The Xbox Kinect system is a sensor based active video game system, which requires body movements to control the game [18].…”
Section: Role Of Exergame On Elderly Performancementioning
confidence: 99%